2014
DOI: 10.3997/1873-0604.2014033
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of fluvial, lacustrine and anthropogenic landforms by means of ground‐penetrating radar (GPR): field experiment

Abstract: A field experiment aiming to study the influence of measurement conditions on depths of penetration and resolution of GPR surveys was conducted in the middle Obra valley (western Poland). The tests were carried out along five profile lines in three sites representing fluvial, lacustrine and anthropogenic landforms. The GPR surveys were conducted at various hydrogeological conditions: high and low groundwater levels, and in winter conditions when the ground was under snow/ice cover and frozen. The best measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
(140 reference statements)
0
5
0
1
Order By: Relevance
“…Marking the sand by the faint or lack of reflections may be the effect of increased silt content in these deposits (cf. Słowik, ). Moreover, they appear at 10–35 m of section 46 marking peat and gyttja (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Marking the sand by the faint or lack of reflections may be the effect of increased silt content in these deposits (cf. Słowik, ). Moreover, they appear at 10–35 m of section 46 marking peat and gyttja (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The base of the channel corresponds to an erosional surface overlaid by the sand deposits rich in wood fragments constituting the channel fill. Many studies identified similar characteristics in their study areas (see, e.g., Vandenberghe and Van Overmeeren, 1999;Lunt et al, 2004;Słowik, 2014a).…”
Section: Discussionmentioning
confidence: 99%
“…Slowik [62] demonstrated that the depths of penetration were highest at low groundwater levels but the depth range containing useful information was the same as at high water levels. Furthermore, Slowik [65] conducted GPR on fluvial, lacustrine and anthropogenic landforms to determine the influence of hydrogeological conditions, silt content and measurements parameter settings on depth range and resolution. He determined that the highest depths of penetration were reached at low groundwater levels but some sedimentary structures were better imaged at high groundwater levels.…”
Section: Discussionmentioning
confidence: 99%